Nickel(II)‐Mediated C−S Cross‐Coupling Between Thiols and ortho‐Substituted Arylboronic Acid. Issue 3 (25th January 2021) - Hanaya, Kengo; Ohtsu, Hiroyoshi; Kawano, Masaki; Higashibayashi, Shuhei; Sugai, Takeshi
Abstract: Herein, we report a C−S cross‐coupling reaction between alkyl thiols or aryl thiols and ortho ‐substituted arylboronic acids that proceeds in the presence of an inexpensive and ligand‐free NiCl2  ⋅ 6H2 O salt and N ‐methylmorpholine, a weak base, at 25 °C in air. The presence of coordinating and electron‐withdrawing groups at the ortho ‐position of the arylboronic acids played a crucial role in determining the efficiency of the reaction. X‐ray crystallographic analysis revealed that the [NiCl2 (DMF)2 (H2 O)2 ] complex was formed in‐situ . The complex is an excellent precursor of the active nickel species. The reaction offers an extremely mild and operationally convenient method to access a wide variety of alkyl aryl sulfides and diaryl sulfides without using expensive transition metals, such as palladium, gold, and rhodium, and specialized and expensive ligands. Abstract : A ligand‐free and inexpensive Ni(II) complex promotes the C−S cross‐coupling reaction between thiols and arylboronic acids, having coordinating groups at their ortho ‐positions. The reactions proceed in the presence of a weak base, in air under mild and convenient reaction conditions at 25 °C.